2015
DOI: 10.1186/s12887-015-0368-x
|View full text |Cite
|
Sign up to set email alerts
|

Attention-deficit/hyperactivity symptoms in preschool children from an E-waste recycling town: assessment by the parent report derived from DSM-IV

Abstract: BackgroundTo investigate the attention-deficit/hyperactivity disorder (ADHD) status among preschool-aged children in Guiyu, an electronic waste (e-waste) recycling town in Guangdong, China.MethodsTwo hundred and forty-three parents were surveyed regarding ADHD behaviors in their children (aged 3–7 years) based solely on the DSM-IV criteria. The peripheral blood samples were taken from these children to measure blood lead levels (BLLs) and blood cadmium levels (BCLs).Results12.8% of children met the criteria fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…This nding suggests that toxic substances in e-waste besides lead may inhibit Hb synthesis and contribute to anaemia pathogenesis. Our previous study in this investigation group showed that there was a negative correlation between blood cadmium and Hb level in children in Guiyu [10], which is consistent with other ndings that the Hb level in the high-cadmium group was lower than that in the low-cadmium group [27].…”
Section: Comparison Of In Uencing Factors Of Anaemia Among Children Isupporting
confidence: 92%
See 1 more Smart Citation
“…This nding suggests that toxic substances in e-waste besides lead may inhibit Hb synthesis and contribute to anaemia pathogenesis. Our previous study in this investigation group showed that there was a negative correlation between blood cadmium and Hb level in children in Guiyu [10], which is consistent with other ndings that the Hb level in the high-cadmium group was lower than that in the low-cadmium group [27].…”
Section: Comparison Of In Uencing Factors Of Anaemia Among Children Isupporting
confidence: 92%
“…The linear correlation coe cient of the lead standard calibration curve was 0.9920. The accuracy of the method was controlled by the use of recoveries between 96% and 108% [10].…”
Section: Measurement Of Bllsmentioning
confidence: 99%
“…Within the studies that used European populations, one used a German population [37], one a Spanish population [38] and one a Belgian population [39]. The other studies used an American population [35,46,48], a Chinese population [34,40], a Turkish population [49] and a Mexican population [33].…”
Section: Resultsmentioning
confidence: 99%
“…Huang and coauthors [33] have shown that blood lead levels among Mexican children with low exposure (≤5 μg/dL) were positively associated with hyperactive/impulsive behaviors but not with inattentiveness. Zhang and coauthors [34] investigated the ADHD status among preschool-aged children in Guiyu, an electronic waste (e-waste) recycling town in Guangdong, China. The study showed that children with high BLLs (≥10 µg/dL) had a 2.4 times higher risk of ADHD than those with low BLLs (<10 µg/dL).…”
Section: Resultsmentioning
confidence: 99%
“…Of the developing countries, China deserves to be highlighted for its biggest population of children living in such a huge area with diversity in geography and culture. While recent studies with ADHD children in China addressed the genetic and environmental influences on ADHD, 7 12 family risk factors for ADHD, 13 and psychological and social interventions of ADHD, 14 , 15 there is a relative shortage of epidemiological studies on ADHD in China.…”
Section: Introductionmentioning
confidence: 99%